Electromechanical coupling analysis of three-dimensional braided piezoelectric composites energy harvester. Issue 27 (14th December 2022) - Meng, Lingfei; Li, Anqing; Wei, Gaofeng
Abstract: In this article, three-dimensional (3-D) braided composite material is used to design the piezoelectric energy harvester in view of its excellent mechanical properties. The energy harvesting model of 3-D braided piezoelectric beam composed of two piezoelectric layers and a 3-D braided composites elastic layer is established. The material properties of 3-D braided composites designed according to the four-step braiding process are obtained by performing finite element analyses on its representative unit. Vibration characteristics and output responses of this energy harvester are investigated in detail and the comparison trend between theoretical and simulated results shows good consistency.